Innovation Capacity, Industrial Structure, and Regional Development of High Quality: Empirical Research Based on the County Level - Chuhao Zhao; Hui Yao (Journal of Function Spaces)
The key to China's regional high-quality development lies in county-level coordination and promotion. Therefore, based on 2847 county-level administrative units in China, this paper uses empirical analysis methods such as dynamic spatial panel Dobbin model and intermediary effect model to study.Then we test the relationship between the industrial structure of county innovation capacity and regional development of high quality. The results showed that (1) the regional development of high quality at the county level in China was generally distributed in clusters, and the agglomeration had a further trend of strengthening. (2) The innovation ability and industrial structure also had a positive effect on the regional development of high quality at the county level, and the result was significant. (3) Innovation had both direct and indirect effects on regional development of high quality. Industrial structure and regional development of high quality had strong spatial and temporal dependence effects.